Statins and ischaemia reperfusion injury: a molecular biological review - Abdul Rahman, Mohd Norhisham Azmi; Chetter, Ian Clifford (Bentham Science Publishers B.V., 2010)
The 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase inhibitors (statins) are a class of drug used to lower low-density lipoprotein (LDL) levels. However, in recent years, statins have been shown to possess a pleiotropic effect beyond its cholesterol lowering ability, including attenuating the effect of ischaemia reperfusion injury. This review considers the biomolecular processes that may lead to this beneficial effect.